2022
DOI: 10.1161/cir.0000000000001092
|View full text |Cite
|
Sign up to set email alerts
|

Management of Patients at Risk for and With Left Ventricular Thrombus: A Scientific Statement From the American Heart Association

Abstract: Despite the many advances in cardiovascular medicine, decisions concerning the diagnosis, prevention, and treatment of left ventricular (LV) thrombus often remain challenging. There are only limited organizational guideline recommendations with regard to LV thrombus. Furthermore, management issues in current practice are increasingly complex, including concerns about adding oral anticoagulant therapy to dual antiplatelet therapy, the availability of direct oral anticoagulants as a potential alternative option … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
142
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(150 citation statements)
references
References 131 publications
4
142
0
4
Order By: Relevance
“…35 Anticoagulant users are at increased ICH risk, and the additional knowledge of individual genetic ICH risk could influence clinical decision making in situations with limited evidence or equivocality of clinical parameters. For potential cardioembolic sources of ischemic stroke such as left ventricular aneurysm, 8 ventricular thrombus, 36 or low ejection fraction, 37 anticoagulation indications are controversial, but also for well-established indications such as deep venous thrombosis, pulmonary embolism, and cerebral sinus thrombosis, duration of anticoagulation is uncertain and provoked versus unprovoked status can be ambiguous. [5][6][7][8][9] Randomized controlled trials validating bleeding risk scores are missing, but the clinical utility is demonstrated by the mentioning of HAS-BLED in American and European guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…35 Anticoagulant users are at increased ICH risk, and the additional knowledge of individual genetic ICH risk could influence clinical decision making in situations with limited evidence or equivocality of clinical parameters. For potential cardioembolic sources of ischemic stroke such as left ventricular aneurysm, 8 ventricular thrombus, 36 or low ejection fraction, 37 anticoagulation indications are controversial, but also for well-established indications such as deep venous thrombosis, pulmonary embolism, and cerebral sinus thrombosis, duration of anticoagulation is uncertain and provoked versus unprovoked status can be ambiguous. [5][6][7][8][9] Randomized controlled trials validating bleeding risk scores are missing, but the clinical utility is demonstrated by the mentioning of HAS-BLED in American and European guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…5 The off-label use of direct oral anticoagulants (DOAC) has become an attractive alternative in this setting due to their lack of need for monitoring and dose adjustments. 6 DOACs have become contemporary treatments for other cardiovascular conditions including non-valvular atrial fibrillation, in which their efficacy is similar to VKA, despite lower rates of bleeding. 2 However, it is currently unclear whether DOACs have similar efficacy as VKA in terms of reducing the risk of systemic embolism including stroke and thrombus resolution in the setting of LV thrombus.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,5,7 The current approaches to managing incidence of LVT include use of Vitamin K antagonists (VKA) and/or Direct oral anticoagulants (DOAC) until resolution of the thrombus (~3 to 6 months). 1,5,[7][8][9] Although recent clinical approaches show preferential use of DOAC over VKA, due to better patient compliance and drug safety issues (reduced bleeding and limited adverse drug interactions). [10][11][12][13] Currently the following five DOAC are available to be used for the prevention of thrombosis, i.e., dabigatran, rivaroxaban, apixaban, edoxaban, and betrixaban.…”
Section: Introductionmentioning
confidence: 99%